Renal unit characteristics and patient education practices that predict a high prevalence of home‐based dialysis in Australia. Issue 9 (September 2014) - Fortnum, Debbie; Ludlow, Marie; Morton, Rachael L
Abstract Aim The proportion of patients using home dialysis in Australia varies from 6% to 62% between renal units. The aim of this study was to determine if the variance is attributed to any underlying renal unit factors including pre‐end stage education practices. Methods An online survey was distributed to all Australian units that offered home dialysis. Logistic regression was performed to estimate the effects of renal unit characteristics on the binary outcome of <30% versus ≥30% of patients using home dialysis, and for ≥10% of patients using home haemodialysis (HHD) dialysis specifically. Prevalent home dialysis rates were sourced from the Australia and New Zealand Dialysis and Transplant Association registry. Results 33 of 43 units (77%) completed the survey. Factors shown to predict ≥30% of patients using home dialysis were; a metropolitan based renal unit compared with a rural or remote unit (OR 1.08, 95% CI 1.01–1.15), a New South Wales unit compared with other states (OR 1.13, 95% CI 1.04–1.22), and a unit that offered multiple group education sessions per year (OR 1.01, 95% CI 1.01–1.02). A unit that offered >1 h of pre‐end stage education per patient, compared with ≤1 h predicted more than 10% of patients on HHD (OR 2.84, 95% CI 1.17–6.90). Conclusion Our data suggest certain pre‐end stage education practices are significantly associated with home dialysis rates above the national average. The consistent above average home dialysis rates witnessed in New South Wales appear to be the result of renal unit culture, education strategies and policies that support 'home dialysis first'.